2014
DOI: 10.1371/journal.pone.0103856
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Metabolic Syndrome Risk in Valproate-Treated Patients with Epilepsy and the General Population in Estonia

Abstract: BackgroundNo study has explored the risk of metabolic syndrome (MS) in patients with epilepsy treated with valproate (VPA) at the population level. The aim of this study was to compare the risk of MS in VPA-treated patients in Estonia to the risk in the general population.MethodsThis study involved 118 patients with epilepsy (63 men, 55 women) who received VPA monotherapy. MS was diagnosed according to the National Cholesterol Education Program Adult Treatment Panel III criteria. Data were compared with the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
1
11
2
Order By: Relevance
“…Despite this lack of statistical significance, the trend showing more hypertension in patients with structural and unknown etiology leads us to conclude that more studies are needed to clarify a finding that could be clinically relevant. (Rakitin et al, 2014) and did not differ from other AEDs such as CBZ in another report (Rakitin, Kõks, & Haldre, 2016). In our study, VPA had the lowest CRF PRc, and taking into account these recently published results, we considered that using it as the reference AED would not cause major confusion.…”
Section: Discussionsupporting
confidence: 58%
“…Despite this lack of statistical significance, the trend showing more hypertension in patients with structural and unknown etiology leads us to conclude that more studies are needed to clarify a finding that could be clinically relevant. (Rakitin et al, 2014) and did not differ from other AEDs such as CBZ in another report (Rakitin, Kõks, & Haldre, 2016). In our study, VPA had the lowest CRF PRc, and taking into account these recently published results, we considered that using it as the reference AED would not cause major confusion.…”
Section: Discussionsupporting
confidence: 58%
“…The aim of this study was to determine whether treatment with VPA or CBZ is correlated with MetS development and risk of IR in epileptic patients. The ndings of our study showed that, VPA treatment approximately increased the risk of MetS based on IDF criteria 19 times more than the control, There are several studies conducted on the signi cant effect of VPA on the development of MetS [2,12,13,36] Rakitin et al reported that, the risk of MetS did not increase in 118 epileptic patients who received the VPA as monotherapy [1]. The NCEP criteria was used for evaluation of MetS risk in Rakitin's study.…”
Section: Discussionmentioning
confidence: 58%
“…On the other hand, CBZ therapy showed signi cant correlation with IR risk based on HOMA index only. Most studies have used the HOMA index, and they have reported signi cantly increased values of IR in VPA-treated cases [1,2,36,48]. However, Naja et al [19] studied the VPA-treated Iranian patients and they reported that there were normal values of insulin and no evidence of IR in VPA-treated as case and CBZ -treated as controls and this nding has also been supported by a study conducted by Kwan et al [49].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, this study lacked a control group of patients not taking VPA, and this result was similar to those reported in other studies carried out in obese patients who were not treated with VPA ( 21 ). Other researchers reported similar frequencies of MS between VPA-treated adults and control subjects ( 15 , 23 , 24 ). A study evaluating the prevalence of MS among Chinese adult obese patients with epilepsy treated with VPA showed a tendency toward a higher risk of MS compared to obese control subjects, without reaching the level of statistical significance ( 25 ).…”
mentioning
confidence: 53%